2016
DOI: 10.1016/j.bbamem.2016.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Polyglutamine aggregates impair lipid membrane integrity and enhance lipid membrane rigidity

Abstract: Lipid membranes are suggested as the primary target of amyloid aggregates. We study aggregates formed by a polyglutamine (polyQ) peptide, and their disruptive effect on lipid membranes. Using solution atomic force microscopy (AFM), we observe polyQ oligomers coexisting with short fibrils, which have a twisted morphology that likely corresponds to two intertwined oligomer strings. Fourier transform infrared spectroscopy reveals that the content of β-sheet enriched aggregates increases with incubation time. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 63 publications
1
23
0
Order By: Relevance
“…We have previously used this method to evaluate changes in bilayer permeability caused by different compounds. 3840…”
Section: Resultsmentioning
confidence: 99%
“…We have previously used this method to evaluate changes in bilayer permeability caused by different compounds. 3840…”
Section: Resultsmentioning
confidence: 99%
“…But the exact mechanism of hIAPP-induced membrane disruption is far from clear. And numerous models have been described during recent years [ 38 41 ]. A report concluded that soluble oligomers from several types of amyloids, including hIAPP, specifically increase lipid bilayer conductance, while the soluble low molecular weight species have no effect, suggesting that this may represent the common primary mechanism of pathogenesis in amyloid-related diseases, such as AD, PD and diabetes [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental procedure has been described elsewhere. 2123 Briefly, mica supported planar bilayers are formed by injecting SUVs into the AFM liquid cell using a syringe pump. Once a complete bilayer is formed (~20 min), 10 mM HEPES at pH 7.0 is injected to remove excess SUVs.…”
Section: Methodsmentioning
confidence: 99%